2020
DOI: 10.1186/s12909-020-1980-5
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress and burnout in caring for older adults during medical school training

Abstract: Background: Moral distress is a reason for burnout in healthcare professionals, but the clinical settings in which moral distress is most often experienced by medical students, and whether moral distress is associated with burnout and career choices in medical students is unknown. We assessed moral distress in medical students while caring for older patients, and examined associations with burnout and interest in geriatrics. Methods: A cross-sectional survey study of second-, third-, and fourth-year medical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…For example, moral distress can be perceived differently based on an individual’s place in the organizational hierarchy [ 26 ] or due to the power differential between different professions [ 27 ]. Other studies suggest power and hierarchy play a role in both moral distress and moral courage [ 8 , 17 , 27 , 28 ]. In one study that explored moral courage in nursing students, most students cited power differential, fear of consequences, and lack of confidence as key influences contributing to their hesitation to demonstrate moral courage, often remaining as passive spectators [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, moral distress can be perceived differently based on an individual’s place in the organizational hierarchy [ 26 ] or due to the power differential between different professions [ 27 ]. Other studies suggest power and hierarchy play a role in both moral distress and moral courage [ 8 , 17 , 27 , 28 ]. In one study that explored moral courage in nursing students, most students cited power differential, fear of consequences, and lack of confidence as key influences contributing to their hesitation to demonstrate moral courage, often remaining as passive spectators [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals can experience moral distress when their values conflict with their workplace. The consequences of moral distress can be lasting [ 5 , 6 ] and include feelings of powerlessness, sadness, anger, frustration [ 7 ], and burnout [ 8 ]. There are several other terms that are relevant to the phenomenon of moral distress.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The results of previous studies have shown that MD among nurses reduces the quality of working life, which can eventually lead to leaving the profession. 9,[15][16][17][18] Nearly all nurses experience MD at some point in their career, but nurses who worked in critical care units seem more at risk for experiences of MD due to challenges in their work environment. 12,14 Critical care nurses often encounter various ethical dilemmas, probably due to more experience in the frequency of providing palliative and end-of-life care, 19,20 excessive workload, direct observation of patients' pain and suffering, 21 uncertainty in clinical decision-making, [22][23][24][25] and conflicts with other healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…Moral distress and burnout received particular focus in relation to health care professionals, as they spend most of their time providing care to people who are vulnerable by definition and place further pressure on their decisions [17,18]. Although MD received particular attention among nurses [16,19], physicians [14,20], physical therapists [21], and further healthcare assistants are also exposed to the same risks [22]. Feelings associated with the experience of MD include anger, guilt [23], and helplessness [24], which seem to occur more frequently during the early years of employment, where a discontinuity between the ideals of the profession and the harshness of daily work is often perceived [20,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Although MD received particular attention among nurses [16,19], physicians [14,20], physical therapists [21], and further healthcare assistants are also exposed to the same risks [22]. Feelings associated with the experience of MD include anger, guilt [23], and helplessness [24], which seem to occur more frequently during the early years of employment, where a discontinuity between the ideals of the profession and the harshness of daily work is often perceived [20,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%